Reviews - Philip Barker; Brian Boullier; Kate Garland; Bruce Ingraham; John Robertson; Mantz Yorke (Association for Learning Technology, 2000)
Most people involved in teaching and learning will have a number of Websites that they use in order to store and disseminate electronic materials. In my own case, for example, I have a research Website, several personal sites, an organizational Web location and several intranets. I use the latter for providing controlled access to both my teaching and learning materials and my library of 'cherished' electronic documents. Increasingly, as people move from paper-based to electronic writing, there will be a growing need actively to promote those sites that they feel are important for other people to know about. This useful 'little book' by Martin Kenprovides a number of helpful suggestions for achieving this.